2023
DOI: 10.4314/asr.v7i1.23132
|View full text |Cite
|
Sign up to set email alerts
|

Third Worldism and Internationalism

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Clearly, the NIEO was faced with a number of important (perhaps insurmountable) constraints, not the least was the flaw of its leaders who often used the rhetoric of a 'common front' not so much to actually hold the West to account but to justify their own domestic malpractices or economic crises by placing the entire blame on the West. Thus it has been argued that, ever since the Bandung Conference in 1955, the rhetoric of cooperation was used more as a tool of 'electoral realpolitik [than] as ideological call to arms' (Nash, 2004). Perhaps the culmination of Bandung's aims in the NIEO demonstrated that South-South cooperation 'did not result in any lasting political alliance or structure' (Nash, 2004).…”
Section: A Case Study In South-south Cooperation: the New International Economic Ordermentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, the NIEO was faced with a number of important (perhaps insurmountable) constraints, not the least was the flaw of its leaders who often used the rhetoric of a 'common front' not so much to actually hold the West to account but to justify their own domestic malpractices or economic crises by placing the entire blame on the West. Thus it has been argued that, ever since the Bandung Conference in 1955, the rhetoric of cooperation was used more as a tool of 'electoral realpolitik [than] as ideological call to arms' (Nash, 2004). Perhaps the culmination of Bandung's aims in the NIEO demonstrated that South-South cooperation 'did not result in any lasting political alliance or structure' (Nash, 2004).…”
Section: A Case Study In South-south Cooperation: the New International Economic Ordermentioning
confidence: 99%
“…Thus it has been argued that, ever since the Bandung Conference in 1955, the rhetoric of cooperation was used more as a tool of 'electoral realpolitik [than] as ideological call to arms' (Nash, 2004). Perhaps the culmination of Bandung's aims in the NIEO demonstrated that South-South cooperation 'did not result in any lasting political alliance or structure' (Nash, 2004). Perhaps more importantly (in terms of strategy) is the fact that the debt crisis of the early 1980s (fuelled by the effects of the commodity crash and oil boom of the 1970s and the western regrouping around neoliberal fundamentals), allowed the members of the NIEO to be unilaterally picked off one-by-one.…”
Section: A Case Study In South-south Cooperation: the New International Economic Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth underscoring that Ramaphosa's righteous plea is made not only on behalf of his country, but also on behalf of his continent. This is in stark contrast with the vaccine nationalism expressed by leaders of the world's richest countries, and is evocative of third worldism described by Andrew Nash as significantly flawed but nonetheless “as viable a model as we have of revolutionary internationalism as a living force, an ethos of consciously shaping ideas and actions not through pronouncements from above, but through building links of solidarity, exchanging ideas, developing common resources and engaging in collective action” ( 24 ). This ethos is something that we find inspiring in the example of the mRNA Hub.…”
Section: The Solidarity-sovereignty Nexusmentioning
confidence: 93%
“…Young's central argument is that Third Worldism, a form of socialist internationalism which sought to dismantle western economic and political hegemony over postcolonial states (Nash, 2003, 95), formed an important part of North Korea's foreign policy and national identity construction. This allowed Kim Il Sung to establish economic and political relationships with emerging postcolonial states, export his Juche ideology and personality cult, and bolster North Korea's international recognition vis-à-vis South Korea.…”
mentioning
confidence: 99%